Solvothermal DMSO-mediated synthesis of the S/AgI micro-/nano-structures and its application as photocatalytic and biological agents (International Journal of Biology and Chemistry, 2022)
S/AgI microstructures were produced by solvothermal DMSO-mediated synthesis using two methods of sulfur precipitation: at room temperature (method 1) and by water (method 2). The samples were obtained with different percentages of AgI: 10, 30 and 50 %. Microstructures were investigated with help of XRD, Raman spectroscopy and SEM/EDS (elemental mapping). XRD and Raman spectroscopy confirmed the presence of sulfur and AgI. EDS elemental mapping revealed that samples were composed of large grains of sulfur covered by smaller grains of AgI. The obtained SEM micrographs revealed that the 1st method gave larger grains of sulfur in comparison with the 2nd method. Testing of the microstructures as photocatalysits showed the low activity; as the prepared samples were able to degrade no more than 7 % of the molecules of Orange II. Significant biological activity was detected only for S/AgI (2) 50 % sample, as it was able to suppress test strains of S. aureus ATCC ВАА-39, P.aeruginosa ATCC 9027 and Erwinia amylovora at MBC/MFC 5000 µg/mL, and E. coli ATCC 8739 at 2500 µg/mL.